Study of Blood Glucose and Serum Calcium Level in Small For Gestational Age Babies (Journal of Shaheed Suhrawardy Medical College, 2013)
Background: Incidence of hypoglycemia in small for gestational age (SGA) babies is high. Therefore small for gestational age babies need close biochemical monitoring of blood glucose for early diagnosis and immediate management of hypoglycemia to prevent future neurodevelopmental outcome. Objectives: The study was designed to measure blood glucose and serum calcium level in new born babies with SGA and to compare with normal new born babies. Methodology: This case control study was done in Neonatology Department of BSM Medical University, Dhaka from 01 July to 31 December 2006. Low birth weight newborn babies with birth weight below 10th centile for gestational age were considered as SGA babies whereas babies with gestational age more than 37 completed weeks and weight more than 2500 gm were considered as control group. Results: Thirty two cases and equal number of controls were studied. Among 32 babies with SGA, hypoglycemia was found in 46.9% of cases and 3.1% cases in control group which was statistically significant (P